Biodegradable biopolymer electrolyte from sugar palm fiber-derived carboxymethyl cellulose doped with ammonium thiocyanate: electrical and physicochemical studies - Azhan, Adlin Umairah; Rani, Mohd Saiful Asmal; Awang Kechik, Mohd Mustafa; Kadir, Mohd Fakhrul Zamani; Hanibah, Hussein; Holilah, Holilah; Shamsudin, Intan Juliana (Springer Science and Business Media Deutschland GmbH, 2026)
A novel biodegradable biopolymer electrolyte (BPE) was developed using carboxymethyl cellulose (CMC) derived from sugar palm fiber, addressing the need for sustainable and eco-friendly electrolyte materials. The BPE films were prepared by incorporating various weight percentages (0, 10, 20, 30, and 40 wt%) of ammonium thiocyanate (NH₄SCN) as a charge carrier via the solution casting technique. The molecular interaction, structural, electrical, and electrochemical properties of the films were characterized using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Electrochemical Impedance Spectroscopy (EIS), Transference Number Measurements (TNM), and Linear Sweep Voltammetry (LSV). The highest ionic conductivity at ambient temperature was achieved at with the sample containing 30 wt% NH₄SCN. XRD analysis confirmed the increasing amorphousness of samples with the addition of more NH₄SCN. FTIR and TNM results indicated that proton (H⁺) conduction dominated due to interactions between CMC and the ammonium salt. The LSV analysis showed an electrochemical stability window of approximately 2.2 V, suggesting the potential of this BPE film as an electrolyte in proton batteries. This study’s novelty lies in utilizing sugar palm fiber-derived CMC doped with ammonium thiocyanate, demonstrating enhanced proton conduction in a biodegradable polymer matrix, which has not been extensively explored in prior works.